Analisis Perencanaan Supply Chain Management Pada PT. Sinar Galesong Peratama - Mhd Yahya; Dina Aulia Nasution; Zerimah Afgani Hasibuan; Siti Aisyah (Universitas Labuhanbatu, 2022)
Supply chain management is needed by companies because it helps the company development process. Supply chain management includes the process of supplier selection, logistics planning, and supply distribution. The purpose of this study is to determine the process of supplier selection, logistics planning and distribution logistics at PT. Sinar Galesong Pratama Manado. This study uses a qualitative approach that focuses on the analysis of supply chain management plans. The result of this survey is the supplier selection process at PT. Sinar Galesong Pratama cooperates with PT, the only agent in Indonesia that owns the Suzuki brand Indomobil Suzuki Sales. Logistics plan at PT. Suzuki Indomobil has the highest sales in terms of product quality, competitive prices, supplier reliability, time efficiency, location efficiency, and cost efficiency. Distribution of supplies from PT. Sinar Galleson Platama Ask a shop that cooperates in selling genuine Suzuki spare parts to support the sales process of PT Management because the catchment area is wide in North Sulawesi. Sinar Galesong Pratama can build a new factory in the Sulawesi region. For example, at KAPET Bitung, the goal is to enable faster logistics services and delivery in the North Sumatra region.